A brief glimpse at CTRP3 and CTRP9 in lipid metabolism and cardiovascular protection. (October 2016) - Yang, Yang; Li, Yue; Ma, Zhiqiang; Jiang, Shuai; Fan, Chongxi; Hu, Wei; Wang, Dongjin; Di, Shouyin; Sun, Yang; Yi, Wei
Abstract: Adipose tissue is now known to express and secrete numerous adipokines that not only regulate lipid metabolism but also function in a wide array of physiological or pathological processes. C1q tumor necrosis factor-related protein 3 (CTRP3, also known as CORS26/cartducin) and CTRP9, novel members of the adipokine family, have intersecting functions in the regulation of lipid metabolism and contribute to cardiovascular protection. Here, we focus on the novel advances concerning the roles of CTRP3 and CTRP9 in these processes and review the general mechanisms. This review should serve as a basis for the design of future experimental studies and may implicate these adipokines as future therapeutic targets.